A clinical comparative study to assess the efficacy of a new centric registration technique with a conventional technique - R Sushma; Malvika Suresh Roy; Pronob Kumar Sanyal; Anand Joshi; Aaditee Vande; Abhijeet Ramachandra Kore (The Journal of Indian Prosthodontic Society, 2019)
Aim: The aim and objectives of this study were to assess and compare the efficacy of a new copyrighted technique (wax ball technique, L-77997/2018) and design (denture base design for the wax ball technique, L-78006/2018) for recording centric relation (CR). Settings and Designs: In vivo – comparative study. Materials and Methods: This study was conducted on sixty consented edentulous patients. The study participants were divided into Group I and Group II. CR in Group I patients was recorded using Dawson's bimanual technique (technique 1). For participants in Group II, CR was recorded using the authors' copyrighted technique (technique 2). Time taken and accuracy of CR records by both the techniques were evaluated. Statistical Analysis Used: Descriptive statistics such as frequency and percentage were calculated for categorical variables, mean and standard deviation were calculated for quantitative variables. Independent t-test was used to compare the time taken to record the CR between the two groups. The accuracy of both the techniques was assessed by Mann–Whitney U-test. Results: The mean time taken for technique 1 was 56.47 s, whereas for technique 2, it was 5.97 s, with an overall mean difference of 50.5 s between the two techniques. Both techniques were found to be accurate, as the CR recorded during jaw relation matched with CR during trial in all the cases in both the groups (frequency 30 (N) and cumulative percentage 100%). Conclusion: From the study, it was found that, time taken for technique 2 was statistically less compared to that of technique 1, and both the techniques were found to be equally accurate.